2006
DOI: 10.1002/ps.1327
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of QoI resistance in Plasmopara viticola oospores

Abstract: QoI fungicides, inhibitors of mitochondrial respiration at the Qo site of cytochrome b in the mitochondrial bc(1) enzyme complex, are commonly applied in vineyards against Plasmopara viticola (Berk. & MA Curtis) Berl. & De Toni. Numerous treatments per year with QoI fungicides can lead to the selection of resistant strains in the pathogen population owing to the very specific and efficient mode of action. In order to evaluate the resistance risk and its development, two different methods, biological and molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 20 publications
(37 reference statements)
3
32
0
1
Order By: Relevance
“…This fluctuation of resistance resulting from the use strategy of QoIs might be based on a reduced fitness of QoI-resistant isolates, as it was described also by Heaney et al (2000) and Genet et al (2006). Similar declines of Sierotzki et al 2008) resistance after QoI treatments were stopped have also been observed in oospore populations of P. viticola in some vineyards in Italy (Toffolatti et al 2006) and in P. cubensis populations in glasshouses in Japan (Ishii 2003 personal communication). In order to investigate the segregation pattern of QoI resistance, a sensitive P2 and a resistant P1 mating type single sporangiophore isolate (Scherer and Gisi 2006) were crossed by co-inoculating a 1:1 sporangial mixture onto grape leaves.…”
Section: Qoi Fungicidesmentioning
confidence: 60%
“…This fluctuation of resistance resulting from the use strategy of QoIs might be based on a reduced fitness of QoI-resistant isolates, as it was described also by Heaney et al (2000) and Genet et al (2006). Similar declines of Sierotzki et al 2008) resistance after QoI treatments were stopped have also been observed in oospore populations of P. viticola in some vineyards in Italy (Toffolatti et al 2006) and in P. cubensis populations in glasshouses in Japan (Ishii 2003 personal communication). In order to investigate the segregation pattern of QoI resistance, a sensitive P2 and a resistant P1 mating type single sporangiophore isolate (Scherer and Gisi 2006) were crossed by co-inoculating a 1:1 sporangial mixture onto grape leaves.…”
Section: Qoi Fungicidesmentioning
confidence: 60%
“…The application of a QoI mixed with other fungicides does not seem to eliminate selection pressure, but delays it compared to the application of QoI fungicide alone (Toffolatti et al 2007). From a practical point of view, care should be taken not to use QoI fungicides again on plots of land having presented QoI resistance during the growing season, or then to preserve products containing QoIs for rare or selective applications during very strong epidemic pressure, and by alternating treatments with fungicides possessing different mode of action.…”
Section: Fitness Parametersmentioning
confidence: 97%
“…Although a biological test (Wong and Wilcox 2000;Genet et al 1997) or molecular tools have been used to quantify the resistance alleles using real-time q-PCR, ARMS PCR or PCR, (Collina et al 2005;Grasso et al 2006;Toffolatti et al 2007;Sirven and Beffa 2003) or to detect resistant haplotypes using the CAPS method, (Corio-Costet et al 2006;Baudoin et al 2008;Furuya et al 2009) little is known about the fitness of QoIresistant isolates. One study suggested that an artificial P. viticola population containing 5% of resistant isolates tended to increase QoI sensitivity (Genet et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This fluctuation of resistance resulting from the use strategy of QoIs might be based on a reduced fitness of QoI-resistant isolates, as it was described also by Heaney et al (2000) and Genet et al (2006). Similar declines of resistance after QoI treatments were stopped have also been observed in oospore populations of P. viticola in some vineyards in Italy (Toffolatti et al 2006) and in P. cubensis populations in glasshouses in Japan (Ishii 2003 personal communication). In order to investigate the segregation pattern of QoI resistance, a sensitive P2 and a resistant P1 mating type single sporangiophore isolate (Scherer and Gisi 2006) were crossed by co-inoculating a 1:1 sporangial mixture onto grape leaves.…”
Section: Qoi Fungicidessupporting
confidence: 53%